Job-Specific Investment and the Cost of Dismissal Restrictions : The Case of Portugal - Takizawa, H. (IMF Working Papers; Working Paper, 2003)
Using a search and matching labor market equilibrium model, this paper quantifies lost labor productivity and consumption per worker that emerges from the restrictions on dismissals. Dismissal restrictions hamper the efficient reallocation of workers, with workers remaining longer in jobs. But the restrictions also tend to induce job-specific investments. A calibration exercise applied to Portugal suggests that the restrictions on dismissal slow the pace of worker reallocation and cause substantial losses of labor productivity and consumption. Although lower worker mobility induces job-specific investment that offsets part of the labor productivity and consumption losses, the size of this offsetting effect is, at most, modest.